2017
DOI: 10.1039/c7tb01370a
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of paclitaxel and cisplatin with biocompatible PLGA–PEG nanoparticles enhances chemoradiotherapy in non-small cell lung cancer models

Abstract: Chemoradiotherapy (CRT) with paclitaxel (PTX) and cisplatin (CP) is part of the standard of care for patients with locally advanced non-small cell lung cancer (NSCLC). Despite the high treatment intensity, many patients still develop local recurrence after treatment. Thus, there is a strong need to further improve CRT for lung cancer. One strategy is to co-deliver cytotoxic chemotherapy agents using biocompatible nanoparticles (NPs) which can limit off-target tissue toxicity and improve therapeutic efficacy. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…The NextA encapsulated within PLGA nanoparticles (INAPs and NextA-PLGA) retained their ability to inhibit pan-HDAC activity (Figure 4a). This finding is consistent with earlier published reports where encapsulated agents in PLGA particles were shown to work similarly to or better than free agents (Table S3) [4,[7][8][9]. Critically, the activity of NextA was not diminished even in the presence of NIR laser activation, suggesting the compatibility of administering NextA with ICG-based PTT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The NextA encapsulated within PLGA nanoparticles (INAPs and NextA-PLGA) retained their ability to inhibit pan-HDAC activity (Figure 4a). This finding is consistent with earlier published reports where encapsulated agents in PLGA particles were shown to work similarly to or better than free agents (Table S3) [4,[7][8][9]. Critically, the activity of NextA was not diminished even in the presence of NIR laser activation, suggesting the compatibility of administering NextA with ICG-based PTT.…”
Section: Discussionsupporting
confidence: 92%
“…These properties make PLGA an excellent candidate for applications involving the controlled release of encapsulated agents and improved drug pharmacokinetics in vivo [6,7]. Several published studies have demonstrated that loading drugs within PLGA can enhance their functionality over free drugs by improving their pharmacokinetic profiles and decreasing drug thresholds [4,[7][8][9]. For melanoma, recent preclinical studies highlight PLGA as a suitable carrier for immune-stimulating molecules and anti-angiogenic agents [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The NPs offer a platform to co-encapsulate various pairs of drugs with varying hydrophobicity and pharmacokinetic profiles ensuring simultaneous long term distribution to the target site. Such NP co-formulations can extend the drugs’ circulation time ( Tian et al, 2017 ), sustain drug release ( Khuroo et al, 2018 ) and also inhibit development of drug resistance ( Misra and Sahoo, 2011 ) as well as increase drug accumulation in tumors ( Afrooz et al, 2017 ). Among the many combinations co-loaded in one particle are PTX-Cisplatin ( Tian et al, 2017 ), PTX-Erlotinib ( Khuroo et al, 2018 ), DOX-CUR ( Misra and Sahoo, 2011 ), PTX-Verapamil ( Afrooz et al, 2017 ), and PTX-epigallocatechin gallate (EGCG).…”
Section: Combination Treatments With Plga Npsmentioning
confidence: 99%
“…From the results published by Von Hoff and co-workers, it is clear that using a nanoparticle-based delivery system significantly improved the therapeutic potential of the drug compared to the use of the free form of docetaxel. PLGA-PEG nanoparticles, containing two drugs, cisplatin and paclitaxel, as an aid for chemoradiotherapy against non-small cell lung cancers, showed greater tumour inhibition compared to the single-loaded nanoparticle or the drug administration in a free form [96]. Human oral squamous carcinoma cell lines, such as PE/CA-PJ15, were targeted in vitro by a study performed by González-Miró et al, 2018 [90] produced PHB beads by using an inducible expression of a fusion protein composed by a PhaC and a modified, non-toxic pneumolysin equivalent of a virulence factor produced by Streptococcus pneumoniae.…”
Section: Polylactic (Pla) Andmentioning
confidence: 99%